2022
DOI: 10.1123/ijspp.2021-0227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Knowledge of Results and Change-Oriented Feedback on Swimming Performance

Abstract: Purpose: This study examined the effect of providing knowledge of results (KR) with, and without, promotion- and change-oriented feedback on repeated-sprint ability in swimmers. Methods: Twenty-nine male and female swimmers (age = 16 [1] y, height = 1.74 [0.07] m, body mass = 61.0 [8.4] kg) were randomly allocated into 2 different feedback conditions, or a condition without feedback (NoFb), as a crossover, repeated-measures design. In one feedback condition, the swimmers were provided with lap completion times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Based on numerous studies that have demonstrated that KR and KP can improve motor performance in healthy subjects (Doma et al, 2022;Han et al, 2022;Sparrow & Summers, 1992;Zalech & Bujak, 2017) and stroke patients (Chen et al, 2016;Cirstea et al, 2006;Cirstea & Levin, 2007;Kim & Oh, 2019;Molier et al, 2010;Subramanian et al, 2010), we hypothesized that MC could be modified in a similar way.…”
Section: Introductionmentioning
confidence: 99%
“…Based on numerous studies that have demonstrated that KR and KP can improve motor performance in healthy subjects (Doma et al, 2022;Han et al, 2022;Sparrow & Summers, 1992;Zalech & Bujak, 2017) and stroke patients (Chen et al, 2016;Cirstea et al, 2006;Cirstea & Levin, 2007;Kim & Oh, 2019;Molier et al, 2010;Subramanian et al, 2010), we hypothesized that MC could be modified in a similar way.…”
Section: Introductionmentioning
confidence: 99%